A Slight Look Environmental Disclosure Score Trends during Covid-19 Outbreak: What’s Driver the Environmental Disclosure in Indonesian Mining and Manufacturing Companies - Wahyuningrum, Indah Fajarini Sri; Agustina, Linda; Jati, Kuat Waluyo; Amal, Muhammad Ihlashul; Sriningsih, Sriningsih (International Journal of Energy Economics and Policy, 2024)
Amid growing environmental challenges and economic development in developing countries, companies must adopt robust environmental disclosure practices to fulfil their corporate responsibility. This study examines environmental disclosure trends from 2020 to 2022 during the COVID-19 pandemic, specifically focusing on the environmentally sensitive manufacturing and mining sectors selected through purposive sampling. A total of 40 company samples, encompassing 120 units of analysis, underwent analysis involving descriptive statistics, classical assumption tests, and multiple linear regression. The research explores the connection between various variables, such as company size, age, profitability, leverage, share ownership, and audit committee composition, and their impact on environmental disclosure practices. The findings reveal a rising trend in environmental disclosure among manufacturing and mining companies during the COVID-19 and post-pandemic period, increasing from 53.2% in 2020 to 60.8% in 2022. In 2022, the energy, industrial, and health sectors saw increased environmental disclosure, while the basic materials and cyclical consumer sectors decreased. Regression analysis shows that company size, profitability, and audit committees impact environmental disclosure, while company age, leverage, and foreign ownership have no discernible influence. This research provides valuable insights into environmental disclosure in Indonesia’s manufacturing and mining sectors.